2016
DOI: 10.1590/0100-69912016003004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of blood flow pattern after triple stent endovascular treatment of saccular abdominal aortic aneurysm: a porcine model.

Abstract: Objective: to determine the blood flow pattern changes after endovascular treatment of saccular abdominal aortic aneurysm with triple stent. Methods: we conducted a hemodynamic study of seven Landrace and Large White pigs with saccular aneurysms of the infrarenal abdominal aorta artificially produced according to the technique described. The animals were subjected to triple stenting for endovascular aneurysm. We evaluated the pattern of blood flow by duplex scan before and after stent implantation. We used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…Although blood flow retention after stenting was slightly higher with helical stents than with straight stents, the difference between straight and helical stents was not significant with respect to the SD value. The possibility of velocity reduction after stenting was also reported by Oliveira et al in a pig aorta (26). Conversely, de Borst et al performed stenting and velocimetry, but their results showed a reduction in diameter, resulting in a faster velocity than that before stenting (27).…”
Section: Discussionmentioning
confidence: 71%
“…Although blood flow retention after stenting was slightly higher with helical stents than with straight stents, the difference between straight and helical stents was not significant with respect to the SD value. The possibility of velocity reduction after stenting was also reported by Oliveira et al in a pig aorta (26). Conversely, de Borst et al performed stenting and velocimetry, but their results showed a reduction in diameter, resulting in a faster velocity than that before stenting (27).…”
Section: Discussionmentioning
confidence: 71%
“…In all cases, both helical and straight stenting resulted in velocity reductions. Oliveira et al measured average blood flow velocity in the aorta of pigs and found a reduction in velocity after stent placement (10). This velocity reduction may be related to artery expansion by stent placement (11).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Oliveira et al (6), manually manufactured multilayer stents composed of three metallic mesh stents joined together were implanted into swine models with aortic saccular aneurysms of bovine pericardium, in a similar fashion to our methodology, though not employing the Cardiatis MFMS. Although the authors did not evaluate aneurysmal sac thrombosis after aortic explants, a duplex scan was conducted on all subjects, and changes were noted in flow direction, from a whirlwind pattern in the aneurysmal sac to a laminar intra-stent flow, with remarkable differences in peak systolic speed (6).…”
Section: ' Discussionmentioning
confidence: 99%